The integrated information theory of agency. (23rd March 2022) - Desmond, Hugh; Huneman, Philippe
Abstract: We propose that measures of information integration can be more straightforwardly interpreted as measures of agency rather than of consciousness. This may be useful to the goals of consciousness research, given how agency and consciousness are "duals" in many (although not all) respects.